Fabrication of piezoelectric nano-ceramics via stereolithography of low viscous and non-aqueous suspensions. Issue 3 (March 2020) - Wang, Wei; Sun, Jinxing; Guo, Binbin; Chen, Xiaoteng; Ananth, K. Prem; Bai, Jiaming
Abstract: A high-performance piezoelectric nano-ceramic was fabricated through stereolithography of low viscosity and high solid loading ceramic/polymer composite suspensions. Through the proper fitting calculation of experimental data, the maximum theoretical solid loading, rheological and curing behaviors of the suspension system were evaluated and lucubrated. The suspensions with a 40 vol% solid loading of the BaTiO3 nanoparticles displayed shear thinning behavior and a relatively low viscosity of 232 mPa·s at 46.5 s −1 shear rate. After post-process, the 3D printed ceramic specimens showed a nanometer-level grain size with a density of 5.69 g/cm 3, which corresponds to about 95% of the theoretical density. The printed ceramics exhibit a piezoelectric constant of 163 pC/N and relative permittivity of 2762 respectively. The results achieved in this research indicate that the stereolithography process is a promising 3D printing technology to fabricate piezoelectric materials with complex geometries and exquisite features for the applications of ceramic components.